PERBEDAAN POLA BAKTERI PADA PASIEN RINOSINUSITIS KRONIK SEBELUM DAN SESUDAH TERAPI LARUTAN HIPERTONIK DAN ISOTONIK - MIFTAHUL JANNAH; SITI MASLIANA SIREGAR (LP2MTBM MAKARIOZ, 2021)
Chronic rhinosinusitis is a common condition that is defined as inflammation of the nose and paranasal sinuses. Patients withchronic rhinosinusitis experience at least two or more of the following symptoms experienced for 2 weeks. These symptomsinclude nasal congestion, runny nose, pain or pressure in the face, reduced sense of smell (hyposmia). The purpose of thisstudy was to determine differences in bacterial culture before and after administration of hypertonic and isotonic solutions inpatients with chronic rhinosinusitis. This type of research is a purely experimental study with a Rendomized Trial Pre andPost Desaign research design. Based on the results of the analysis test chi square p value was 0.001 which stated that therewas a significant difference between isotonic and hyperonic solutions. There are differences in bacterial culture before andafter hypertonic and isotonic solutions in patients with chronic rhinosinusitis.